Inclure des élèves nouvellement arrivés en France : transformations des acteurs au sein d’une recherche collaborative interprétative - Malgorzata Jaskula; Véronique Miguel Addisu (Recherches en Éducation)
We search to understand how the reflexive actors (practicians and researchers) transform themselves in the collaborative and interpretative research in education and what the domains of these transformations are. This dynamic appears particularly pertinent for the current questions of education. Thanks to the interpretations co-constructed during a long time, the shared reflexivity encourages “the communicational action” of transformation in this paradigm. We will study this dynamic looking into the example of three reflexive practicians based on the research about the inclusion of newly arrived allophones’ students in France. The study reveals that the transformations happen in the heart of the differences and complementarities between the theoretical knowledge and practice. They have got an impact on the professional development of all actors of this research (practicians and researchers), and largely, on the implication in the environment.